Boron bridging of rhamnogalacturonan‐II, monitored by gel electrophoresis, occurs during polysaccharide synthesis and secretion but not post‐secretion. (24th January 2014) - Chormova, Dimitra; Messenger, David J.; Fry, Stephen C.
Summary The cell‐wall pectic domain rhamnogalacturonan‐II (RG‐II) is cross‐linked via borate diester bridges, which influence the expansion, thickness and porosity of the wall. Previously, little was known about the mechanism or subcellular site of this cross‐linking. Using polyacrylamide gel electrophoresis (PAGE) to separate monomeric from dimeric (boron‐bridged) RG‐II, we confirmed that Pb2+ promotes H3BO3‐dependent dimerisation in vitro. H3BO3 concentrations as high as 50 mm did not prevent cross‐linking. For in‐vivo experiments, we successfully cultured 'Paul's Scarlet' rose (Rosa sp.) cells in boron‐free medium: their wall‐bound pectin contained monomeric RG‐II domains but no detectable dimers. Thus pectins containing RG‐II domains can be held in the wall other than via boron bridges. Re‐addition of H3BO3 to 3.3 μm triggered a gradual appearance of RG‐II dimer over 24 h but without detectable loss of existing monomers, suggesting that only newly synthesised RG‐II was amenable to boron bridging. In agreement with this, Rosa cultures whose polysaccharide biosynthetic machinery had been compromised (by carbon starvation, respiratory inhibitors, anaerobiosis, freezing or boiling) lost the ability to generate RG‐II dimers. We conclude that RG‐II normally becomes boron‐bridged during synthesis or secretion but not post‐secretion. Supporting this conclusion, exogenous [3H]RG‐II was neither dimerised in the medium nor cross‐linked to existing wall‐associated RG‐II domains when added to Rosa cultures. In conclusion, in cultured Rosa cells RG‐II domains have a brief window of opportunity for boron‐bridging intraprotoplasmically or during secretion, but secretion into the apoplast is a point of no return beyond which additional boron‐bridging does not readily occur.